2022
DOI: 10.1007/s11101-022-09814-3
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable microalgal biomass production in food industry wastewater for low-cost biorefinery products: a review

Abstract: Microalgae are recognized as cell factories enriched with biochemicals suitable as feedstock for bio-energy, food, feed, pharmaceuticals, and nutraceuticals applications. The industrial application of microalgae is challenging due to hurdles associated with mass cultivation and biomass recovery. The scale-up production of microalgal biomass in freshwater is not a sustainable solution due to the projected increase of freshwater demands in the coming years. Microalgae cultivation in wastewater is encouraged in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 161 publications
1
10
0
Order By: Relevance
“…Screening of microalgae for robust strain selection is a crucial step and several factors are to be considered as screening parameters such as characteristics of wastewater, desired level of treatment efficiency, tolerance of algae to adverse environment, growth, biomass production, nutrient removal, lipid production, self‐flocculation, biosynthesis of secondary products, ease of downstream processing, cost and energy requirements at various stages. [ 21–23 ]…”
Section: Screening Of Microalgal Strains For Integrated Biorefinery A...mentioning
confidence: 99%
“…Screening of microalgae for robust strain selection is a crucial step and several factors are to be considered as screening parameters such as characteristics of wastewater, desired level of treatment efficiency, tolerance of algae to adverse environment, growth, biomass production, nutrient removal, lipid production, self‐flocculation, biosynthesis of secondary products, ease of downstream processing, cost and energy requirements at various stages. [ 21–23 ]…”
Section: Screening Of Microalgal Strains For Integrated Biorefinery A...mentioning
confidence: 99%
“…Recently, microalgae have been attracting attention as a substitute for fossil fuels and as an edible protein. Culturing microalgae in industrial wastewater provides the dual benefits of nutrient removal which prevents eutrophication as well as low-cost biomass production 6 . In addition, we reported that it is possible to cultivate microalgae using animal cell waste medium 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Considerable attention has been focused on optimizing algal cell growth rates using organic C supplements, or even exclusive heterotrophic cultivation ( Lee, 2001 ; Bogaert et al, 2019 ; Pang et al, 2019 ). Support of algal growth by addition of organic C sources can help alleviate light limitation in high density cultures, reduce light requirements, and algae may be able to use organic C sources available as waste products from other processes, possibly improving biomass production efficiency and costs ( Chen et al, 2011 ; Nirmalakhandan et al, 2019 ; Ummalyma et al, 2022 ). Relatively few algal taxa have been examined in laboratory or commercial cultivation ( Luo et al, 2017 ; Nirmalakhandan et al, 2019 ; Wang, He & Young, 2020 ), although green algae which grow fast and tolerate high nutrient concentrations include Chlorella , Chlamydomonas and Scenedesmus species, for which there is also information about growth, physiology and genetics important for researchers.…”
Section: Introductionmentioning
confidence: 99%